Metabolic Stress Index Including Mitochondrial Biomarker for Noninvasive Diagnosis of Hepatic Steatosis - Chang, Jae Seung; Ahn, Jhii-Hyun; Kang, Seong Hee; Koh, Sang-Baek; Kim, Jang-Young; Baik, Soon Koo; Huh, Ji Hye; Lee, Samuel S.; Kim, Moon Young; Park, Kyu-Sang (Frontiers in Endocrinology, 2022)
Background Mitochondrial dysfunction with oxidative stress contributes to nonalcoholic fatty liver disease (NAFLD) progression. We investigated the steatosis predictive efficacy of a novel non-invasive diagnostic panel using metabolic stress biomarkers. Methods Altogether, 343 subjects who underwent magnetic resonance imaging-based liver examinations from a population-based general cohort, and 41 patients enrolled in a biopsy-evaluated NAFLD cohort, participated in the development and validation groups, respectively. Serologic stress biomarkers were quantitated by enzyme-linked immunosorbent assay. Results Multivariate regression showed that waist-to-hip ratio, fibroblast growth factor (FGF) 21, FGF19, adiponectin-to-leptin ratio, insulin, albumin, triglyceride, total-cholesterol, and alanine-aminotransferase were independent predictors of steatosis (rank-ordered by Wald). The area under receiver-operator characteristics curve [AUROC (95%CI)] of the metabolic stress index for steatosis (MSI-S) was 0.886 (0.85−0.92) and 0.825 (0.69−0.96) in development and validation groups, respectively. MSI-S had higher diagnostic accuracy (78.1%−81.1%) than other steatosis indices. MSI-S notably differentiated steatosis severities, while other indices showed less discrimination. Conclusion MSI-S, as a novel non-invasive index, based on mitochondrial stress biomarker FGF21 effectively predicted steatosis. Furthermore, MSI-S may increase the population that could be excluded from further evaluation, reducing unnecessary invasive investigations more effectively than other indices.